Perspektif Etis Ensiklik Laudato Si’ Tentang Budaya Sekali Pakai - Pabubung, Michael Reskiantio; Sitepu, Roberto Reno (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Throw-away culture is a living habit of modern society that views goods as having a relatively short period of use without any desire or effort to recycle or extend the period of use. In this culture, things are easily seen as useless, needing to be replaced by something else, the newest and most updated. This phenomenon received special attention from Pope Francis in his encyclicals, especially Laudato Si, which contains the Church’s Social Teaching, namely “preferential options for the poor”. This ‘disposable’ culture is one of the roots of the environmental crisis, which also has an impact on the social crisis. Why might the “disposable culture” have an impact on the social crisis? Through qualitative research using literature analysis techniques, researchers will answer this main question from the ethical perspective of Laudato Si through three main studies, namely Laudato Si, ‘disposable culture’, and the social crisis in modern society.